Buddha and Christ, Nativity Stories and Indian Traditions. - Thundy (Numen Book Series, 1992)
The infancy narratives of the gospels of Matthew and Luke appear as a magnificent mosaic of allusions not only to the Hebrew Bible but also to Buddhist and Hindu religious traditions. Professor Thundy argues that many details of the infancy gospels as well as the rest of the gospels can be clarified by the Buddhist and Hindu scriptures. In this sense, the gospels are Eastern religious texts. Buddha and Christ covers the following topics in order: methodology of study, priority of Indian texts vis-à-vis Christian gospels, parallels of the birth narratives of Buddha and Jesus, uniqueness of Indian parallels, the Gnostic context of the Christian gospels, and contacts between India and the West in antiquity. Multicultural studies such as this encourage ecumenism and mutual understanding in East-West dialogues as well as reinforcing the view that the gospels should be taken seriously as Eastern religious texts.